ASEAN Centrality: Still Alive and Kicking - Tsjeng, Henrick Zhizhao (2016)
ASEAN centrality has been challenged by the pulls of US-China tensions of late. Developments behind the scenes, and the recent United States-ASEAN Special Leaders’ Summit at Sunnylands, however, demonstrate the continuing validity of the centrality dynamic.